Implicit Contracts: Two Different Approaches - Oliver Gürtler (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
In this paper, I compare two different approaches to model implicit contracting, the infinite-horizon approach typically used in the literature and afinite-horizon approach building on an adverse-selection model. I demonstrate that even the most convincing result of the infinite-horizon approach, namely that implicit contracting is improved, if the discountrate is lowered, does not carry over to the alternative modeling approach. Predictions of the first approach should therefore be handled with care and subject to athorough reinvestigation.
urn:nbn:de:bvb:19-epub-13441-8
Keywords: D82; D83; J33; M52; 330; Trust; finite horizon; infinite horizon; discounting; implicit contracting